Quality of life following stereotactic body radiotherapy versus three-dimensional conformal radiotherapy for vertebral metastases: Secondary Analysis of an Exploratory Phase II Randomized Trial - Sprave, Tetyana; Verma, Vivek; Förster, Robert; Schlampp, Ingmar; Bruckner, Thomas; Bostel, Tilman; El-Shafie, Rami; Nicolay, Nils; Debus, Jürgen; Rief, Harald (Anticancer research, 2018)
BACKGROUND/AIM: This was a prespecified secondary analysis of a randomized trial, which analyzed quality of life (QOL), fatigue, and emotional distress following stereotactic body radiotherapy (SBRT) versus conventional three-dimensional conformal radiotherapy (3DCRT) as part of palliative management of painful spinal metastases. - MATERIALS AND METHODS: Fifty-five patients were enrolled in this single-institutional randomized exploratory phase II trial (NCT02358720). Participants were randomly assigned to receive SBRT (single-fraction 24 Gy) or 3DCRT (30 Gy/10 fractions). QOL (EORTC QLQ-BM22), fatigue (EORTC QLQ FA13), and emotional distress (QSC-R10) at the end of radiotherapy, along with 3- and 6-month follow-up were assessed. - RESULTS: At all recorded time points, there were no significant QOL differences between cohorts, including painful sites, pain characteristics, functional impairment, or psychosocial aspects (p>0.05 for all). There were also no differences in all dimensions of fatigue between groups at each recorded time point (p>0.05 for all). Emotional distress was also similar at three (p=0.248) and six months (p=0.603). - CONCLUSION: Although these results demonstrate that SBRT does not cause worse QOL deteriorations compared to 3DCRT, larger randomized investigations are recommended to corroborate these findings.
Gesehen am 02.04.2020